Weight change during the first week of life and a new method for retrospective prediction of birthweight among exclusively breastfed newborns. (13th February 2022) - Mtove, George; Abdul, Omari; Kullberg, Fanny; Gesase, Samwel; Scheike, Thomas; Andersen, Frederik Mølkjær; Madanitsa, Mwayiwawo; ter Kuile, Feiko O.; Alifrangis, Michael; Lusingu, John P. A.; Minja, Daniel T. R.; Schmiegelow, Christentze
Abstract: Introduction: Identification of low birthweight and small for gestational age is pivotal in clinical management and many research studies, but in low‐income countries, birthweight is often unavailable within 24 h of birth. Newborn weights measured within days after birth and knowledge of the growth patterns in the first week of life can help estimate the weight at birth retrospectively. This study aimed to generate sex‐specific prediction maps and weight reference charts for the retrospective estimation of birthweight for exclusively breastfed newborns in a low‐resource setting. Material and methods: This was a prospective cohort study nested in a clinical trial of intermittent preventive treatment in pregnancy for malaria with either dihydroartemisinin–piperaquine with/without azithromycin or sulfadoxine–pyrimethamine in Korogwe District, north‐eastern Tanzania (Clinicaltrials.gov : NCT03208179). Newborns were weighed at birth or in the immediate hours after birth and then daily for 1 week. Reference charts, nadir, time to regain weight, and prediction maps were generated using nonlinear mixed‐effects models fitted to the longitudinal data, incorporating interindividual variation as random effects. Predictions and prediction standard deviations were computed using a linear approximation approach. Results: Between March and December 2019, 513 live newborns with birthweights measured within 24 h of delivery were weighed daily for 1 week. Complete datasets were available from 476 exclusively breastfed newborns. There was a rapid decline in weight shortly after delivery. The average weight loss, time of nadir, and time to regain weight were 4.3% (95% confidence interval [CI] 3.8–4.9) at 27 h (95% CI 24–30) and 105 h (95% CI 91–120) in boys and 4.9% (95% CI 4.2–5.6) at 28 h (95% CI 23–33) and 114 h (95% CI 93–136) in girls, respectively. The data were used to generate prediction maps with 1‐h time intervals and 0.05 kg weight increments showing the predicted birthweights and weight‐for‐age and weight‐change‐for‐age reference charts depicting variation in weight loss from <1 to >10%. Conclusions: The prediction maps and reference charts can be used by researchers in low‐resource settings to retrospectively estimate birthweights using weights collected up to 168 h after delivery, thereby maximizing data utilization. Clinical practitioners can also use the prediction maps to retrospectively classify newborns as low birthweight or small for gestational age.